PERJAMUAN KUDUS INKLUSI SEBAGAI RUANG HOSPITALITAS BAGI TEOLOGI DISABILITAS - Debbie Tohatta (Bethel Press, 2024)
Hospitality shows an openness toward each person's differences by respecting each other in sincerity. The focus of hospitality lies in sincerity in giving and accepting other people's limitations (Tabita Kartika Christiani). This attitude of accepting other people's limitations reminds us of people with disabilities who, in the view of society and the church, are often used as objects of pity, less involved, abnormal, and considered incapable. The church often does not care about what people with disabilities experience and struggle with. Without realizing it, this attitude of the church has made a difference within the church body itself. People with disabilities should be seen as people with gifts from God. Gifts that enable them to continue their lives together with others. Therefore, so that people with disabilities can recognize their existence, people need to be educated to accept the presence of people with disabilities amid fellowship as part of the body of Christ that cannot be separated. Inclusive Holy Communion can be a friendly space for people with disabilities because all people are united from various backgrounds through Holy Communion. Inclusive Holy Communion helps people understand that everyone is equal before God and has the right to receive salvation from Him. This article invites people to understand that inclusive Holy Communion can help everyone, including people with disabilities, feel accepted and valued in communion with Christ.